Kinematics and dynamics analysis of a novel 2PC-CPR parallel mechanism. (4th October 2016) - Lin, Sheng; Wang, Shuilan; Wang, Chun; Zhang, Lingxuan; Zhai, Yun
A novel parallel mechanism of two translations and one rotation freedom degrees two-prismatic joint-cylindrical joint-one-cylindrical joint-prismatic joint-revolute joint (2PC-CPR) is proposed. The mechanism can be applied to write Chinese characters and to classify productions with the appropriated control. In this article, the kinematics and dynamics analysis are systematically conducted with the following procedure. First of all, the 2PC-CPR parallel mechanism is designed by GF set and the freedom degree of the mechanism is calculated using screw theory. Then the formula for solving the inverse/forward displacement, velocity, and acceleration is derived based on the geometrical constraints. The dynamics model is established by using virtual work principle. Finally, kinematics SimMechanics model is created by the co-simulation of SolidWorks and MATLAB software, and its workspace is analyzed.